Pengaruh Pemberian Gel Doksisiklin terhadap Jumlah Fibroblas pada Proses Penyembuhan Dermatitis Paederus akibat Racun Kumbang Tomcat (Paederus sp.) pada Mencit (The Effect of Doxycycline Gel on The Number of Fibroblast in Paederus Dermatitis Healing - Silvi Ahmada Chasya; Al Munawir; Erma Sulistyaningsih (Pustaka Kesehatan, 2016)
Paederus dermatitis caused by rove beetle makes the tissue damage called dermonecrosis. The MMP on pederin toxins from the symbiosis of rove beetle (Paederus sp.) and Pseudomonas aeruginosa is supposed can delay the wound healing process. Doxycycline gel as a MMP inhibitor is believed can accelerate the healing process. The purpose of this study was to determine the effect of doxycycline gel on the healing process of Paederus dermatitis by observing the number of fibroblasts as an indicator. This study used 40 mice, were divided into four major groups, those were normal control group, the negative control, treatment groups with doxycycline gel 1% and 5%. Termination was performed on days 1, 3, 5, 7, and 15. Data was obtained by calculating the number of fibroblasts per field of view, then processed in ImageJ and tested statistically with comparation test of One Way Anova. The average number of fibroblasts per field of view in treatment groups was higher. The peak occurred on day 7 and decrease on day 15. It indicated that the topical administration of doxycycline gel on Paederus dermatitis can accelerate healing process, showed by the increasing in average number of fibroblasts per field of view. Keywords: doxycycline gel, fibroblast, paederus dermatitis